Addressing the Challenging Problem of High-Riding NAC after Breast Reduction: A Novel Solution and Review of Techniques - Gupta, Rajat; Bansal, Priya; Neeraj, Neharika (Indian Journal of Plastic Surgery, 2025)
High-riding nipple–areolar complex (NAC) due to postoperative malposition following breast reduction surgery is a very serious aesthetic problem for the patients and a very difficult one for surgeons to correct. Reduction surgeries aim to elevate the NAC, and the best course of action for avoiding a high-riding NAC is prevention of over-elevation, taking care of marking the appropriate distance between the NAC and the inferior mammary fold. Its correction poses a very difficult challenge due to the limited skin between the upper edge of the NAC and the sternal notch and the concern for avoiding scars that lie above the nipple in the superior pole of the breast. There are various techniques described for repositioning the NAC to an acceptable position, but most of them come with the drawback of unsatisfactory correction of bottoming out, additional scars, and multiple stages. A technique of mastopexy called “two-flap technique” including repositioning of the NAC as well as elevation of inferior breast mound (or correction of bottoming out), without any additional scars, is described in this article.
Keywords: breast reduction; high-riding nipple; two-flap technique; mastopexy